Mitochondrial Function and Microbial Metabolites as Central Regulators of Intestinal Immune Responses and Cancer - Weber-Stiehl, Saskia; Järke, Lea; Castrillón-Betancur, Juan Camilo; Gilbert, Felix; Sommer, Felix (Frontiers in Microbiology, 2022)
Energy and anabolic metabolism are essential for normal cellular homeostasis but also play an important role in regulating immune responses and cancer development as active immune and cancer cells show an altered metabolic profile. Mitochondria take a prominent position in these metabolic reactions. First, most key energetic reactions take place within or in conjunction with mitochondria. Second, mitochondria react to internal cues from within the cell but also to external cues originating from the microbiota, a vast diversity of associated microorganisms. The impact of the microbiota on host physiology has been largely investigated in the last decade revealing that the microbiota contributes to the extraction of calories from the diet, energy metabolism, maturation of the immune system and cellular differentiation. Thus, changes in the microbiota termed dysbiosis have been associated with disease development including metabolic diseases, inflammation and cancer. Targeting the microbiota to modulate interactions with the mitochondria and cellular metabolism to delay or inhibit disease development and pathogenesis appears an attractive therapeutic approach. Here, we summarize recent advances in developing the therapeutic potential of microbiota-mitochondria interactions for inflammation and cancer.